Implementing Problem-Based Learning to Improve Social Skills and Social Studies Learning Outcomes among Seventh-Grade Students at SMPN 14 Madiun - Irvan Bintar Kalahari; Sudarmiani Sudarmiani; Nurhadji Nugraha (MASI Mandiri Edukasi, 2026)
An innovative instructional model is needed that can simultaneously integrate the development of social skills and improvements in learning outcomes. This study aims to analyze the implementation of Problem-Based Learning (PBL) in Social Studies instruction to develop social skills and improve the learning outcomes of seventh-grade students at SMPN 14 Madiun. This study adopts a classroom action research (CAR) design conducted in two cycles. Data were collected through observation, testing, and documentation, then analyzed using both quantitative and qualitative approaches. The findings indicate that implementing the PBL model improved students' social skills and learning outcomes. The class average score increased from 65.3 in the pre-cycle to 72.2 in Cycle I and 79.5 in Cycle II, with the learning mastery rate rising from 43.3% to 86.7%. Students' social skills also improved, with the proportion of students achieving good or very good social skills increasing from 26.7% in Cycle I to 93.3% in Cycle II, while the proportion of students in the sufficient category decreased from 73.3% to 6.7%. This study concludes that the PBL model is an effective instructional approach in Social Studies for enhancing students' learning outcomes and social skills.